Retrospective Study of Ellipsoid Zone Integrity Following Treatment with Intravitreal Ocriplasmin (OZONE Study) - Drenser KA (Dove Medical Press, 2021)
Kimberly A Drenser,1 Dante J Pieramici,2,3 Joseph M Gunn,4 Daniel F Rosberger,5 Petra Kozma,6 Mitchell S Fineman,7,8 Luc Duchateau,9 Arshad M Khanani10 1Associated Retinal Consultants P.C., Royal Oak, MI, USA; 2California Retina Consultants, Santa Barbara, CA, USA; 3California Retina Research Foundation, Santa Barbara, CA, USA; 4Southeastern Retina Associates, Kingsport, TN, USA; 5Weill-Cornell Medical College; MaculaCare, PLLC, New York, NY, USA; 6Oxurion NV (formerly ThromboGenics NV), Leuven, Belgium; 7Mid Atlantic Retina, Philadelphia, PA, USA; 8Wills Eye Hospital, Philadelphia, PA, USA; 9Ghent University, Ghent, Belgium; 10Sierra Eye Associates, Reno, NV, USACorrespondence: Kimberly A DrenserAssociated Retinal Consultants P.C., 3555 W 13 Mile Road# LL-20, Royal Oak, MI, 48073, USATel +1 248 288 2280Fax +1 248 288 5644Email kdrenser@arcpc.netPurpose: To assess generalized (GD) and focal ellipsoid zone disruption (FD) in patients with symptomatic vitreomacular adhesion (sVMA) using spectral domain optical coherence tomography (SD-OCT) following ocriplasmin.Patients and methods: OZONE was a Phase 4, retrospective study of patients with sVMA treated with a single intravitreal injection of ocriplasmin (0.125 mg). Data from adult patients with at least 6-month follow-up after ocriplasmin were included. SD-OCT was performed at baseline (within 30 days before ocriplasmin), before Day 21 post-injection (early observation, EO), and by last observation (LO) which was maximally 6 months post-injection. The main outcome measure was the development of new and the evolution of existing FD/GD at EO and LO.Results: The study enrolled 134 eyes/patients from 22 sites in the USA. At baseline, 87 eyes (64.9%) had FD, 21 eyes (15.7%) had GD and 26 eyes (19.4%) had no FD/GD. Among the eyes without FD/GD at baseline, 13 (50%) and 8 (30.8%) developed FD or GD, respectively, by EO. By LO, FD/GD improvement or resolution was seen in > 80% of these eyes. Among the eyes with FD/GD at baseline, < 40% had improving/resolving EZ integrity at LO. The absence of FD/GD at baseline was associated with less persistent FD/GD at LO (P< 0.0005). The presence of FD with MH at baseline was associated with persistent FD at LO (P=0.027).Conclusion: The fact that a large majority of eyes had FD/GD prior to ocriplasmin was unexpected and demonstrates that EZ disruptions are common in sVMA. This suggests that loss of EZ integrity may be part of the natural history of this disorder. It is hypothesized that the status of the EZ at baseline is a contributing, ocriplasmin independent modulator of subsequent EZ changes after ocriplasmin. Prospective analyses which include a sham control group would be required to test this hypothesis.Keywords: symptomatic vitreomacular adhesion, vitreomacular traction, spectral domain optical coherence tomography, macular hole